COOPERATIVE TEACHING AND REPRODUCTIVE LEARNING - Pljakić, Goran (Metodička teorija i praksa, 2025)
Cooperative teaching has long been one of the leading pedagogical strategies aimed at creating conditions in educational institutions that will contribute to their release from the transmissive teaching model. In accordance with the above, the goal of the research is to identify, among the basic elements of cooperative teaching, those that can be used to predict the level of students' choose to using reproductive learning strategies. The research sample included 516 elementary school students from Serbia, from the Rasina and Pomoravlje districts. The research results confirmed that based on a more successful organization of cooperative teaching, lower levels of student chuse to using reproductive learning can be predicted. The following elements of the structure cooperative teaching stood out as significant predictors in the model: positive interdependence students and “face-to-face“ promotive interaction. Hierarchical regression analysis confirmed that the above variables also have a mediating role in the relationship between the remaining predictors and the criterion variable. Moderator analysis determined that there is an interaction between significant predictor variables in the model. Including this interaction in the regression model increased its accuracy. In its final form, the model of the listed predictors explains 11.1% of the variance in reproductive learning.
Keywords: basic elements of cooperative teaching; reproductive learning; hierarchical regression analysis; moderator analysis